Prevalence of Intestinal Parasites amongst selected age groups within Okada, South –South Nigeria. - Osazee Ekundayo Izevbuwa; Obhioze Augustine Akpoka; Ebere Julein Okafor-Elenwo (International Journal of Applied Biology, 2020)
This study was conducted to determine the prevalence of intestinal parasites from volunteered individuals in the study site. A total of 300 stool samples, comprising 150 females and 150 males were collected randomly from the study population in Ovia North-East Local Government Area in Edo State, aged between 1 and 60 years. The stool samples were aseptically collected and examined using both direct smear method and formol ether sedimentation techniques to determine the individual parasite load of the sampled population. The age group of 16-20 had the highest number of participants 102(34%) while the age group of 6-10, 51-55 and 56-60 had the least number of participants of 3(1%) respectively. Out of the 300 stool samples examined 87, (29%) were positive with intestinal parasites while 213(71%) were negative, not having any intestinal parasitic infection However the age group of 11-15(N=10) and 31-35(N=10) had the highest prevalence rate of 11.5%, while the lowest prevalence (1%) was found in individuals of ages 41-60 years. There was no intestinal parasites found among the individuals below11 years of age.. Of the 150 male candidates examined, 57 (65.5%) were infected with intestinal parasites. On the other hand, their female counterparts had a total prevalence of 34.5%. A total number of six parasitic species were isolated from the fecal specimens. These were Ascaris lumbricoides, Trichuris trichiura, Strongyloides stercolaris, Entamoeba coli, Hookworms and Entamoeba histolytica. Ascaris lumbricoides had the highest prevalence rate (12%), while Trichuris trichiura and Strongyloides stercolaris had the least prevalence rate (1%) respectively. The intestinal parasite infection and age were negatively correlated and there was a significant difference between the male and female infection rates (p<0.05).